Optimization studies on extraction of phytocomponents from betel leaves; Resource-Efficient Technologies; Vol. 3, iss. 4 - Muruganandam L; Anantha Krishna; Jashwanth Reddy; Nirmala G. S. (2017, 2017)
Title screen